STUDI KUALITATIF RESIKO PENULARAN HIV/AIDS MELALUI PENGGUNAAN TATO DI KECAMATAN SEMARANG TENGAH KOTA SEMARANG - Erna Kusumawati; Agustin Rahmawati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Background: The incidence of HIV / AIDS has increased. HIV / AIDS Case in Semarang throughout 2013 reached 396 people, while the findings of AIDS as many as 69 patients, and five patients of whom died. Risk factors HIV/AIDS through sexual contact, sharing needles or body painting together. Distribution of the spread of HIV / AIDS cases on average are spread in Semarang District East, Semarang District of North and Central District of Semarang.Objective: To identify the risk of transmission of HIV / AIDS through a tattoo in the Middle District of Semarang, Semarang City. Methods: The study is a qualitative research study focused on the experience, the interpretation and meaning of life a person who experienced it. Selection of the sample in this study was taken snowball sampling. The number of informants in this study as many as four people to be primary informant and as many as two people to be secondary informant. Results and Discussion: The results showed the majority of informants using a tattoo just for fun, show identity as male and follow the lifestyle. Practice the use of tattoos done demonstrated the use of needles alternated, not sterile and tattoo inks used are not recommended as printer ink, ink pens etc. Most of the informants in the practice of tattoos in places that do not have permission to provide these services and with modest equipment. Most informants less determine whether they wear tattoos that can transmit HIV / AIDS. Most of the informants did not receive complete information about HIV / AIDS. Suggestion: public health workers should be able to provide information about the health especially the spread of HIV / AIDS by providing counseling or disseminate information by providing leafet and make a booklet about VCT and HIV / AIDS.Keywords : Tatoos Practice, HIV/AIDS